23+3x=(x+8)

Simple and best practice solution for 23+3x=(x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 23+3x=(x+8) equation:



23+3x=(x+8)
We move all terms to the left:
23+3x-((x+8))=0
We calculate terms in parentheses: -((x+8)), so:
(x+8)
We get rid of parentheses
x+8
Back to the equation:
-(x+8)
We get rid of parentheses
3x-x-8+23=0
We add all the numbers together, and all the variables
2x+15=0
We move all terms containing x to the left, all other terms to the right
2x=-15
x=-15/2
x=-7+1/2

See similar equations:

| 71=n/7+62 | | -4+7j=-4-4j | | 273=7(2n=3) | | 5x+7x-18=66 | | (8)=5-9x | | 16+2n=4-n | | p-6/2=2 | | p(3p+2)(p-4)=0 | | x+6+89+40=180 | | 1/3y-16=2 | | 3(3x+5)=7x-3 | | -6(5x+3)=132 | | -4(6+v)=-80 | | (5x-3x)/3=-22 | | 2x+x+10=37 | | -5n=–6n+8 | | 6x-15+x+15=5x+10 | | -10p-12=16-3p | | 3(2x+5)+4x=96 | | -4(3-x)=12 | | -3x+18=78+7x | | 2h=-3-h | | 39=13(14-x) | | -s-1=s-21 | | −26/33=13/11x | | 5(x-4)-3=-23 | | 252=204-x | | 14=3+5x-4 | | 12x-4=4(3x+9) | | 7x-3=4x/5 | | 5(2x+1)+9x=12+6(4x-3) | | -6g-8=-10g |

Equations solver categories